Brominated and phosphate flame retardants (FRs) in indoor dust from different microenvironments: Implications for human exposure via dust ingestion and dermal contact. (October 2017) - Zheng, Xiaobo; Qiao, Lin; Covaci, Adrian; Sun, Runxia; Guo, Huiying; Zheng, Jing; Luo, Xiaojun; Xie, Qilai; Mai, Bixian
Abstract: Indoor dust has been widely used to monitor flame retardants (FRs) in indoor environment, but most studies only focused on floor dust. In the present study, FRs were examined in indoor dust from different locations. Dust from air conditioner (AC) filters, beddings, floor, and windows in bedrooms, and dust from AC filters, printer table surface, computer table surface, floor, and windows in offices were collected, respectively. Polybrominated diphenyl ether congener 209 (BDE 209) and decabromodiphenyl ethane (DBDPE) were the most abundant brominated flame retardants (BFRs), and tris(chloroisopropyl) phosphate (TCIPP), tris(1, 3-dichloroisopropyl) phosphate (TDCIPP), and triphenyl phosphate (TPHP) were the most abundant phosphate flame retardants (PFRs). In bedrooms, the AC filter dust had the highest median levels of BDE 209 (536 ng/g) and DBDPE (2720 ng/g), while bed dust had the highest median levels of ΣPFRs (2750 ng/g) among dust samples. In offices, printer table dust had higher median levels of BDE 209 (1330 ng/g), DBDPE (8470 ng/g), and ΣPFRs (11, 000 ng/g) than those in other dust samples. The high dust ingestion values of BDE 209, DBDPE, and individual PFR were 0.28, 1.20, and <0.01–0.32 ng/kg bw/day and 7.37, 31.2, and <0.01–4.54 ng/kg bw/day for BDE 209, DBDPE, and individual PFR for adults and toddlers, respectively. The high dermal exposure values of individual PFR during sleeping were <0.01–0.23 and <0.01–0.36 ng/kg bw/day for adults and toddlers, respectively. More human exposure pathways other than dust ingestion should be considered, such as the dermal contact with beddings and furniture. Highlights: FRs were measured in different types of indoor dust in bedrooms and offices. AC filter dust and bed dust were main reservoirs of FRs in bedrooms. Dust from printer table surface had higher FR levels than other dust in offices. Dermal exposure to FRs via contact with beddings should be further investigated.